A single pseudouridine on rRNA regulates ribosome structure and function in the mammalian parasite Trypanosoma brucei - K. Shanmugha Rajan; Hava Madmoni; Anat Bashan; Masato Taoka; Saurav Aryal; Yuko Nobe; Tirza Doniger; Beathrice Galili Kostin; Amit Blumberg; Smadar Cohen-Chalamish; Schraga Schwartz; Andre Rivalta; et al. (Nature Communications, 2023)
Abstract Trypanosomes are protozoan parasites that cycle between insect and mammalian hosts and are the causative agent of sleeping sickness. Here, we describe the changes of pseudouridine (Ψ) modification on rRNA in the two life stages of the parasite using four different genome-wide approaches. CRISPR-Cas9 knock-outs of all four snoRNAs guiding Ψ on helix 69 (H69) of the large rRNA subunit were lethal. A single knock-out of a snoRNA guiding Ψ530 on H69 altered the composition of the 80S monosome. These changes specifically affected the translation of only a subset of proteins. This study correlates a single site Ψ modification with changes in ribosomal protein stoichiometry, supported by a high-resolution cryo-EM structure. We propose that alteration in rRNA modifications could generate ribosomes preferentially translating state-beneficial proteins.